Use of a Sulfa Desensitization Protocol in Solid Organ Transplant Recipients. (4th October 2017) - Kirsch, Denise; Olyaei, Ali; Wiegel, Joshua; Strasfeld, Lynne
Abstract: Background: Trimethoprim–sulfamethoxazole (TMP-SMX) is first-line for pneumocystis prophylaxis in solid organ transplant (SOT) recipients. TMP-SMX also offers the advantage of urinary tract infection (UTI) prophylaxis (for kidney recipients) and activity against other opportunistic infections. Alternatives for sulfa allergic patients are inferior from the standpoint of pneumocystis protection, activity against other opportunistic infections and cost. Methods: In 2013, our SOT program adopted a system-wide protocol for TMP-SMX desensitization during the index transplant hospitalization. Patients with a historical non-anaphylactic allergy were exposed to increasing doses of TMP-SMX and monitored for allergic reaction. If tolerated, they received standard prophylaxis with TMP-SMX. We completed a retrospective chart review of all patients identified for desensitization. We performed a cost analysis to estimate cost savings associated with the protocol. Results: Forty-three patients were identified and consented for the desensitization protocol. Thirty-eight (88%) were kidney recipients and the remainder were liver or heart recipients. See Figure 1 for pre-desensitization historical allergies. Thirty-six (84%) did not have an allergic reaction during desensitization; 33 ultimately completed 3 months of TMP-SMX prophylaxis; 7 had non-serious allergic or other reactions either during desensitization or before completing 3 months of prophylaxis (Figure 2). See Table 1 for details of reactions. Based off approximate average wholesale prices for 3 months of standard prophylaxis dosing of TMP-SMX (65), pentamidine (600) and nitrofurantoin (220), we estimated a savings of 755 per kidney recipient, comparing TMP-SMX to an alternative of pentamidine and nitrofurantoin (for UTI prophylaxis for kidney recipients). Conclusion: Systematic, protocol-driven TMP-SMX desensitization during index transplant hospitalization is safe and effective in SOT recipients, with resultant cost savings and broader spectrum coverage than second line agents. Disclosures: L. Strasfeld, Merck: Independent Contractor, Salary